2019
DOI: 10.1177/2055102919891396
|View full text |Cite
|
Sign up to set email alerts
|

The use of generic avoidant coping scales for psychosocial adaptation to chronic illness and disability: A systematic review

Abstract: This systematic review examined the validity of generic coping-with-stress measures in the relationships between avoidance-type coping and psychosocial adaptation to chronic illness and disability. Major data bases were searched for studies on the association between avoidance-type coping and psychosocial adaptation to chronic illness and disability. Findings indicated that reliance upon avoidance-type coping is linked to reports of poorer psychosocial adaptation. The veracity of these findings must be treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 167 publications
(244 reference statements)
1
16
0
1
Order By: Relevance
“…Emotion-and avoidance-oriented coping styles may lead to burnout or depression (Sears, Urizar and Evans, 2000, p. 56). Furthermore, a systematic review (Livneh, 2019) indicated that avoidance-oriented coping is linked to reports of poorer psychosocial adaptation to chronic illness and disability. This coping style was found to be particularly ineffective in reducing physical and emotional distress, depression, and anxiety, when confronting stressful life events and health-related conditions.…”
Section: Coping With Stressmentioning
confidence: 99%
“…Emotion-and avoidance-oriented coping styles may lead to burnout or depression (Sears, Urizar and Evans, 2000, p. 56). Furthermore, a systematic review (Livneh, 2019) indicated that avoidance-oriented coping is linked to reports of poorer psychosocial adaptation to chronic illness and disability. This coping style was found to be particularly ineffective in reducing physical and emotional distress, depression, and anxiety, when confronting stressful life events and health-related conditions.…”
Section: Coping With Stressmentioning
confidence: 99%
“…Avoidance explained the association between the baseline vulnerability and the degree of distress measured at 12 months. Coping by avoidance has been linked to poorer psychosocial adaptation according to a systematic review published in 2019 (Livneh, 2019 ). The use of avoidance coping is largely ineffective when confronting stressful life events and health-related conditions.…”
Section: Emotional Healthmentioning
confidence: 99%
“…The use of avoidance coping is largely ineffective when confronting stressful life events and health-related conditions. Furthermore, the reliance on avoidance strategies have been linked to poorer adaptation in a wide range of disorders (Livneh, 2019 ). Interventional studies targeted to reduce avoidance in women who have Overt POI are indicated.…”
Section: Emotional Healthmentioning
confidence: 99%
“…Toutefois, les nombreux travaux menés dans ce domaine évaluent les stratégies de coping en s'appuyant sur des outils génériques comme le Ways of Coping Checklist (Vitaliano, Russo, Carr, & Maiuro, 1985), le Brief Cope (Carver, 1997), le Coping Inventory for Stressful Situations (Endler & Parker, 1990) ou le COPE Inventory (Carver, Scheier, & Weintraub, 1989), utilisés pour mesurer l'adaptation à divers stresseurs rencontrés aussi bien dans le cadre de la maladie, que dans la sphère sociale ou professionnelle. Même s'il a pu être montré un effet délétère des stratégies de coping évitantes ou centrées sur l'émotion des patients atteints de maladies chroniques (Mc Combie, Mulder, & Gearry, 2013), il est important de souligner que les stratégies mesurées à travers ces outils restent limitées à celles classiquement retrouvées dans la population générale et donc discutable au niveau de population vivant des situations spécifiques telles que la maladie (Livneh, 2019). En effet, très peu d'études qualitatives ont permis de mettre en lumière les stratégies déployées par les patients pour faire face à leur MICI (Byron, Cornally, Burton, Savage, 2020).…”
Section: Introductionunclassified